Genetic strategies to analyze primary TRP channel-expressing cells in mice. (November 2017) - Wyatt, Amanda; Wartenberg, Philipp; Candlish, Michael; Krasteva-Christ, Gabriela; Flockerzi, Veit; Boehm, Ulrich
Graphical abstract: Highlights: TRP-IRES-Cre mice enable labeling and manipulation of primary TRP-expressing cells. TRP expression data throughout the organism are needed to interpret global KO mice. TRP-IRES-Cre strains are generated for all 28 mouse TRP channels. Abstract: Transient receptor potential (TRP) ion channels regulate fundamental biological processes throughout the body. TRP channel dysfunction has been causally linked to a number of disease states and thus establishes these channels as promising therapeutic targets. In order to dissect the physiological role of individual TRP channels in specific tissues, a detailed understanding of the expression pattern of the different TRP channels throughout the organism is essential. We provide an overview of recent efforts to generate novel TRP channel reporter mouse strains for all 28 TRP channels encoded in the mouse genome to understand expression of these channels with a single-cell resolution in an organism-wide manner. The reporter mice will enable both the visualization and manipulation of all primary TRP channel-expressing cells allowing an unprecedented wealth in variety to investigate TRP channel function in vivo . As proof of principle, we provide preliminary results documenting TRPM5 expression throughout the entire body of juvenile and adult mice.